Circadian genes and risk of prostate cancer: Findings from the EPICAP study. Issue 7 (12th February 2019) - Wendeu‐Foyet, Méyomo G.; Koudou, Yves; Cénée, Sylvie; Trétarre, Brigitte; Rébillard, Xavier; Cancel‐Tassin, Géraldine; Cussenot, Olivier; Boland, Anne; Bacq, Delphine; Deleuze, Jean‐François; Lamy, Pierre‐Jean; Mulot, Claire; et al.
Abstract : Circadian rhythms regulate several physiological functions and genes controlling the circadian rhythm were found to regulate cell proliferation, cell cycle and apoptosis. Few studies have investigated the role of those circadian genes in prostate cancer occurrence. We aim to investigate the relationship between circadian genes polymorphisms and prostate cancer risk based on data from the EPICAP study, a population‐based case–control study including 1, 515 men (732 cases / 783 controls) with genotyped data. Odds Ratios (ORs) for association between prostate cancer and circadian gene variants were estimated for each of the 872 single nucleotide polymorphisms (SNPs) in 31 circadian clock genes. We also used a gene‐based and pathway‐based approach with a focus on the pathway including 9 core circadian genes. Separate analyses were conducted by prostate cancer aggressiveness. The core‐circadian pathway ( p = 0.0006) was significantly associated to prostate cancer, for either low ( p = 0.002) or high ( p = 0.01) grade tumor. At the gene level, we observed significant associations between all prostate cancer and NPAS2 and PER1 after correcting for multiple testing, while only RORA was significant for aggressive tumors. At the SNP‐level, no significant association was observed. Our findings provide additional evidence of a potential link between genetic variants in circadian genes and prostate cancer risk. Further investigation is warranted to confirm these findings and to better understand the biological pathways involved. Abstract : What's new? Since the publication of the International Agency for Research on Cancer Monograph that classified shift work involving circadian disruption as probably carcinogenic to humans, few epidemiological studies have investigated the role of circadian genes in cancer, including prostate cancer. Based on data from a population‐based case‐control study including 1, 515 men with genotyped data, here the authors observed an association between polymorphisms in the circadian pathway genes and prostate cancer, using a pathway‐based approach. This association was more pronounced when considering the 9 core genes of the pathway. The findings support a role of the circadian genes in prostate cancer carcinogenesis.